Food security status of Zimbabwean immigrants living in Msunduzi municipality, South Africa during the COVID-19 pandemic - Hlatshwayo, Mavis; Mbombo-Dweba, Tulisiwe Pilisiwe (Asian Development Policy Review, 2024)
The study aims to examine food security status of Zimbabwean immigrants living in Msundizi municipality, South Africa, during the COV-19 pandemic. A cross-sectional study design using a mixed-methods approach was adopted to collect data from 379 randomly selected Zimbabwean immigrants. Food security status was assessed using the Household Food Insecurity Access Scale. Data was analysed using descriptive statistics and logistic regression models. Most immigrants were males (66%), 52.2% were 18–38 years old, and 91.4% were employed. Most respondents (51%) had a tertiary education, and 35.9% earned between R3001 and R4500. The majority of immigrants (75%) were food insecure. Food insecurity was perceived to be due to reduced/loss of employment, socio-political factors such as theft, insecurity/violence, political crisis, lack of land ownership, and high food prices. The age, immigration status, and type of employment were associated with food insecurity. Food insecurity is prevalent among Zimbabwean immigrants living in Msunduzi municipality. There is a need for targeted food security policies that are aimed at increasing availability and access to food among immigrants. The SA government should extend food safety nets to all, regardless of citizen status.